Neolignans isolated from Nectandra leucantha induce apoptosis in melanoma cells by disturbance in mitochondrial integrity and redox homeostasis. (August 2017) - de Sousa, Fernanda S.; Grecco, Simone S.; Girola, Natalia; Azevedo, Ricardo A.; Figueiredo, Carlos R.; Lago, João Henrique G.
Abstract: Six neolignans including three previously undescribed metabolites: 1-[(7R)-hydroxy-8-propenyl]-3-[3′-methoxy-1′-(8′-propenyl)-phenoxy]-4, 5-dimethoxybenzene, 4-hydroxy-5-methoxy-3-[3′-methoxy-1′-(8′-propenyl)phenoxy]-1-(7-oxo-8-propenyl)benzene and 4, 5-dimethoxy-3-[3′-methoxy-1′-(8′-propenyl)phenoxy]-1-(7-oxo-8-propenyl)benzene were isolated from twigs of Nectandra leucantha Nees & Mart (Lauraceae) using bioactivity-guided fractionation. Cytotoxic activity of isolated compounds was evaluated in vitro against cancer cell lines (SK BR-3, HCT, U87-MG, A2058, and B16F10), being dehydrodieugenol B and 4-hydroxy-5-methoxy-3-[3′-methoxy-1′-(8′-propenyl)phenoxy]-1-(7-oxo-8-propenyl)benzene the most active metabolites. These compounds displayed IC50 values of 78.8 ± 2.8 and 82.2 ± 3.5 μM, respectively, against murine melanoma. Different in vitro mechanism of induced cytotoxicity for this cell line is proposed for both compounds. Obtained results indicated a remarkable effect during the induction of morphological, biochemical and enzymatic features of apoptosis, such as disruption of mitochondrial membrane potential (ΔΨm), exposure of phosphatidylserine in the outer cell membrane, and genomic DNA condensation and fragmentation. Dehydrodieugenol B induced caspase-3 and PARP activation and 4-hydroxy-5-methoxy-3-[3′-methoxy-1′-(8′-propenyl)phenoxy]-1-(7-oxo-8-propenyl)benzene downregulated the levels of Bcl-2 protein. These effects were accompanied by increased levels of reactive oxygen species as a consequence of mitochondrial damage, followed by F-actin aggregation during the cell death process. Dehydrodieugenol B showed oxidative properties and both compounds, especially 4-hydroxy-5-methoxy-3-[3′-methoxy-1′-(8′-propenyl)phenoxy]-1-(7-oxo-8-propenyl)benzene, displayed potential to alkylate nucleophiles, suggesting an accessory mechanism of tumor-induced cytotoxicity by these metabolites. Graphical abstract: Image 1 Highlights: Six neolignans were isolated from twigs of Nectandra leucantha. Isolated compounds were evaluated in vitro against cancer cell lines. Bioactive compounds displayed IC50 values of 78.8 and 82.2 μM against B16F10 cell lines. Bioactive neolignans induced intrinsic apoptosis.